STUDY THE EFFECT OF PARTIAL FISTULECTOMY WITH ARKAKSHIR BASED KSHARSUTRA LIGATION IN TREATMENT OF BHAGANDARA (FISTULA IN ANO) – A PILOT STUDY (International Journal of Ayurveda and Pharma Research, 2020)
In Ayurveda, Bhagandara (Fistula-in-ano) is included under the Ashtomahagada (eight major diseases) because it is difficult to manage medicinally as well as surgically. Ksharsutra is the potent treatment in Bhagandara routinely practiced by Ayurvedic surgeons but time period required to cut the tract is too long. Hence now-a-days this procedure is modified as partial fistulectomy with Ksharsutra ligation. Ksharasutra was prepared as per API guidelines. Snuhikshir is replaced by Arkakshir and remaining ingredients same as standard Ksharsutra preparation. Methodology: A total 15 patients of Fistula in ano were enrolled for partial fistulectomy with Arkakshir based Ksharsutra ligation under spinal anaesthesia. Since post-operative day 1, patients were advised for Sitz bath with Triphala decoction daily twice a day. Daily dressing with betadine was done. Proper Laxative Gandharvaharitakivati 2 HS was given to relieve constipation. One week later old Ksharsutra was replaced with the new one with gradual tightening of Arkakshir based Ksharsutra by rail-rolled technique. Result: Encouraging effects of partial fistulectomy with Arkakshir based Ksharsutra was noted. Pain, discharge, post-operative wound was significantly reduced. Average Unit Cutting Time (UCT) of fistula tract was 7.68 days/cm. Incontinence and recurrence weren’t found in any case in this study. Conclusion: Partial fistulectomy with Arkakshir based Ksharsutra application is said to be the safe and best procedure which promotes early wound healing with sphincter saving method and least recurrence rate.